Coaches` knowledge and management of eating disorders: a randomized controlled trial - Martinsen, M.; Sherman, R. T.; Thompson, R. A.; Sundgot-Borgen, J. (Medicine & Science in Sports & Exercise, 2015)
Purpose: It has been suggested that programs regarding early identification and prevention of eating disorders (ED) among athletes are unlikely to succeed without their coaches` endorsement and participation. Therefore, we developed a 1-yr intervention aiming to prevent the development of ED among adolescent elite athletes by targeting athletes and their coaches. The separate part of the intervention targeting the coaches was designed to provide knowledge and strategies regarding healthy nutrition, eating behavior, and ED (symptoms, identification, management, and prevention). In this trial, we examined the effect of the educational program on the coaches` knowledge and management index in three content areas (nutrition, weight regulation, and ED). We also examined their subjective evaluation of their ED knowledge.